Islamic Education Reform: Integrating Tradition and Modern Pedagogy - Elinda Novita Dewi; Mahfud Heru Fatoni; Afkarul Azmi; Ainur Rofiq Sofa; Achmad Afif Fikri; Khodijah Asshofiah; Fitrahtul Saahira Khairunnisa (Indonesian Journal of Sharia and Islamic Sciences, 2026)
Islamic education is increasingly challenged to remain relevant amid rapid social, technological, and cultural transformations. This article examines Islamic education reform through the integration of traditional Islamic scholarship and modern pedagogical approaches, highlighting its implications for curriculum development, teaching practices, and socio-cultural outcomes. Using a qualitative normative approach based on contemporary literature, this study analyzes how integrative reform models enable Islamic educational institutions to respond to globalization while maintaining their epistemological and ethical foundations. The findings indicate that integrating tradition and modern pedagogy enhances graduate adaptability, ethical competence, and social engagement without undermining religious identity. Furthermore, the reform supports institutional sustainability by aligning educational goals with societal expectations and global educational standards. This study argues that integrated Islamic education reform is not merely a pedagogical adjustment but a comprehensive transformation that redefines the role of Islamic education in modern Muslim societies. The article contributes to the broader discourse on educational reform by positioning Islamic education as a dynamic system capable of balancing continuity and change